BOT-04 POSSIBLE INVOLVEMENT OF CHLORIDE INTRACELLULAR CHANNEL PROTEIN 2 (CLIC2) IN THE SUPPRESSION OF INVASIVE ACTIVITY OF BRAIN TUMORS. (16th December 2019) - Ozaki, Saya; Inoue, Akihiro; Nishikawa, Masahiro; Suehiro, Satoshi; Kunieda, Takeharu
Abstract: Chloride intracellular channel protein 2 (CLIC2) belongs to the CLIC family of conserved metazoan proteins. However, CLIC2 is the least studied among its family members, and its function remains to be elucidated. Recently, we have shown that CLIC2 is correlated with the development and/or maintenance of tight junctions in blood vessel endothelial cells in human non-cancer tissues. CLIC2-expressing endothelial cells supposedly prevent hematogenous spread of cancer cells. In this study, we investigated CLIC2 expression in human brain tumor tissues and also addressed its function by employing human meningioma cells, rat glioma cells and rat malignant brain tumor model. Thirty-one meningioma cases, six SFT/HPC cases, twelve pituitary adenoma cases and twenty-three glioblastoma cases who underwent surgery at Ehime University Hospital were included. CLIC2 mRNA expression levels were investigated with immunoblotting and quantitative RT-PCR. Cells from the meningiomas were cultured and their CLIC2 expression was knockdown. Filter-based invasion assays and gelatin zymography were performed using the knocked-down meningioma cells. Rat C6 glioma cells stably expressing rat CLIC2 were established and transplanted into the right striatum of neonatal Wistar rats. Effects of CLIC2 on the survival periods of the animals were investigated. CLIC2 expression levels were high in the low-grade cases but low in the high-grade cases and highly invasive cases. Meningioma cells, of which CLIC2 expression was knocked-down, showed higher invasive activity than control cells. The CLIC2-knock down cells displayed increased activities of MMP-2 and MMP-9. Rat brain tumor models revealed that high expression of CLIC2 was correlated with smaller and less invasive brain tumors compared with those consisted of control cells. The rats transplanted with CLIC2-expressing cells survived longer periods than the rats with control C6 cells. These results suggest that CLIC2 plays a role in suppression of invasive activities of tumor cells.